Seasonal Variations and Sexual Differences in Home Range Sizes and Activity Patterns of Endangered Long-Tailed Gorals in South Korea - Sangjin Lim; Maniram Banjade; Jaeyong Ahn; Dongju Song; Jangick Son; Yungchul Park (Animals)
The long-tailed goral (Naemorhedus caudatus) faces significant threats from habitat loss and fragmentation and is classified as a Class I endangered species by the Ministry of Environment in South Korea and vulnerable by the IUCN. Understanding the behavioral ecology of this species is crucial for effective conservation and protective measures. Using GPS collars, this study investigated the home range sizes and activity patterns of nine rehabilitated long-tailed gorals (four males and five females) across three regions (Yanggu, Seoraksan National Park, and Uljin) from 2014 to 2016. The 95% minimum convex polygon (MCP) home range averaged 0.64 ± 0.33 km2, while the 50% MCP home range averaged 0.15 ± 0.05 km2. The male home ranges were larger than the female home ranges. Additionally, the home ranges varied seasonally, with the smallest recorded in winter. The activity pattern of long-tailed gorals was predominantly crepuscular and diurnal, with no significant sexual differences. There were no significant differences in activity during spring, summer, and autumn; however, activity in winter differed significantly from that in the other seasons. The data provided on the home ranges and activity patterns of the species will serve as a basis for developing effective conservation and management strategies to protect this endangered species. By elucidating the spatial and temporal behaviors of long-tailed gorals, this study enhances our understanding of the ecological needs of the species and helps develop precise conservation measures.